Perbedaan Pencapaian Kompetensi Farmakoterapi pada Ujian OSCE Mahasiswa FKIK Universitas Warmadewa Semester 7 dan 8 - Adelia Putri Mas; Rima Kusuma Ningrum; Luh Gde Evayanti (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2025)
Pharmacotherapy is a sub-discipline of pharmacology that studies the treatment of diseases through the use of medications. The use of drugs is considered rational when patients receive medications that suit their needs, for an adequate period of time, and at the most affordable cost for both the patient and society. Prescription writing falls under the competency of healthcare physicians, meaning that doctors are required to master the proper and correct way of writing prescriptions. The Objective Structured Clinical Examination (OSCE) is part of an assessment system aimed at evaluating the clinical competencies and skills of students objectively and systematically. This study aims to determine the differences in the achievement of pharmacotherapy competency during the OSCE among 7th and 8th-semester students of the Faculty of Medicine and Health Sciences, Warmadewa University. The method used in this research is a descriptive-analytic method to identify the relationship between variables through a cross-sectional approach. The target population in this study consists of all medical students of the Faculty of Medicine and Health Sciences at Warmadewa University who meet the inclusion and exclusion criteria. Data collection was based on OSCE scores from the 2019 cohort. A dependent t-test was then conducted, followed by determining Cohen's d. The dependent t-test results showed that the average OSCE scores in pharmacotherapy competence in the 7th and 8th semesters were significantly different, with a p-value of 0.000. This improvement from the 7th to the 8th semester reflects a deeper mastery of more complex pharmacotherapy scenarios.